Molecular Characterization of Sarcocystis Species Isolated from Sheep and Goats in Riyadh, Saudi Arabia - Metwally, Dina M. (Animals (Basel), 2019)
SIMPLE SUMMARY: In this article, we investigated the occurrence of Sarcocystis species in samples of sheep and goats obtained from slaughterhouses in Riyadh, Saudi Arabia. We searched for tongue, heart, esophagus, diaphragm and skeletal muscle tissues. Fragments of these tissues were investigated by macroscopic evaluations, direct optical microscopy of tissue fragments, optical microscopy of digested fragment sediment, transmission electron microscopy and PCR followed by nucleotide sequencing. From the set of information obtained, we searched 230 sheep, and 84 goats; 91 and 36 were found to be infected, respectively. Transmission electron microscopy (TEM) revealed Sarcocystis tenella (S. tenella) in sheep and Sarcocystis capracanis (S. capracanis) in goats. Sarcocystis species were confirmed in Saudi Arabian sheep and goats by molecular testing. S. capracanis was most closely related to S. tenella, with the mitochondrial cytochrome c oxidase subunit I gene (COX1) sequences sharing a (91.7%) identity. ABSTRACT: Sarcocystosis is induced by species of Sarcocystis, which is an intracellular protozoan parasite in the phylum Apicomplexa. The diversity and importance of Sarcocystis species in sheep and goats in Saudi Arabia are poorly understood. In this study, the tongue, esophagus, heart, diaphragm, and skeletal muscles were collected from 230 sheep and 84 goats, and the tissues were examined for the presence of Sarcocystis species by macroscopic examination and light microscopy. Microscopic Sarcocystis species cysts were found in both sheep and goats. Transmission electron microscopy (TEM) revealed S. tenella in sheep and S. capracanis in goats. Sarcocystis species were confirmed for the first time in Saudi Arabian sheep and goats by molecular testing. S. capracanis was most closely related to S. tenella, with the COX1 sequences sharing 91.7% identity. A phylogenetic analysis produced similar results and indicated that the Sarcocystis isolates were within a group of Sarcocystis species in which dogs were the final host. Finally, the Sarcocystis species cysts from sheep and goats could be grouped together, indicating that they were strongly related.